Comparison of sandblasted, ground and melt-etched zirconia crowns regarding adhesion strength to resin cement - Kvam, Ketil (Biomater Investig Dent, 2019)
Objectives: The aim is to compare the adhesion between zirconia and cements attained with melt-etching with potassium hydrogen difluoride, KHF(2), with that found when such traditional surface treatments as sandblasting and ceramic stone grinding are employed. Materials and methods: Groups of zirconia crowns where treated by sandblasting (n = 6), grinding with carbide bur (n = 6) or melt-etching with KHF(2) (n = 6) of the surface before cementation with a resin cement to an implant substitute made by Selective Laser Melting of a cobalt-chromium alloy. Tensile testing was performed to rupture, while measured increasing load at the zirconia-cement interface. The strength was calculated by dividing the rupture load with the contact area. The three groups were compared using one-way ANOVA. Results: The adhesion strength between the zirconia crowns and the cement resulted in significant differences between all groups (p < .05). The sandblasted group had the lowest strength (5.2 ± 0.95 MPa), the ground group significantly higher (7.3 ± 1.49 MPa) and the melt-etched group the highest values (9.8 ± 1.37 MPa). Conclusion: The adhesive strength of resin cement to zirconia can be ranked according to the surface preparation with surfaces melt-etched with KHF(2) stronger than ground which is stronger than sandblasted.